Methodology to improve profitability in a company textile industry through the improvement of the recruitment process and selection of human resources using Lean Six Sigma and Digital Transformation (LACCEI, 2024)
Micro, small and medium enterprises MIPYMES) represent 90% of the companies incorporated in the world, its importance is such that they generate between 60% and 70% employment and 50% of GDP the Peruvian case is not different from this context since MSMEs generate 85% of employment and contribute to 84% of GDP. These companies develop their productive and commercial activity in different economic sectors among which is the textile and clothing this sector the which represents 7.2% of the gross domestic product (GDP), concentrates approximately 700,000 workers and comes growing at rates of 40% average in recent years. Without However, despite the dynamism and importance of this sector, the productivity is extremely low this is due to different factors, one of these being human capital management this factor is related to poor selection processes, recruitment and training of personnel, which makes it difficult for these companies have at all times workers who have with competencies required to perform in the processes production and thus boost the competitiveness of this sector. For overcome these deficiencies, it has been established as the main objective in the following investigation to implement an agile model and efficient in the selection, hiring and training processes, to reduce staff turnover and contribute to the improvement of productivity based on Digital Transformation and Lean Six Sigma methodology